2009
DOI: 10.1007/s10526-009-9213-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fungicides on Metarhizium anisopliae in the rhizosphere, bulk soil and in vitro

Abstract: The entomopathogenic fungus Metarhizium anisopliae (Metchnikoff) Sorokin (Hypocreales: Clavicipitaceae) is registered in the United States and The Netherlands for black vine weevil, Otiorhynchus sulcatus (Coleoptera: Curculionidae) control in container-grown ornamentals. These studies were conducted to determine the compatibility of M. anisopliae (F52) with a wide range of fungicides commonly applied to container-grown ornamentals for the management of soil-borne plant pathogens. The impact of fungicides on sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 31 publications
3
14
0
2
Order By: Relevance
“…Shah et al [12] reported variation in the inhibitory effect of the fungicides on different fungi. While captan appears to be detrimental to multiple entomopathogenic fungi, strobilurin fungicides, azoxystrobin and pyraclostrobin seem to be compatible with B. bassiana, but not with Metarhizium spp [9,12].…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Shah et al [12] reported variation in the inhibitory effect of the fungicides on different fungi. While captan appears to be detrimental to multiple entomopathogenic fungi, strobilurin fungicides, azoxystrobin and pyraclostrobin seem to be compatible with B. bassiana, but not with Metarhizium spp [9,12].…”
Section: Resultsmentioning
confidence: 93%
“…Sulfur and captan are the most widely used fungicides and in general, fungicide use surpasses that of acaricides and insecticides in California strawberries [2]. Earlier studies by Moorhouse, Gillespie, Seller, and Charnley [6], Jaros-Su, Groden, and Zhang [7], Luz, Netto, and Rocha [8], and Brook [9] evaluated the impact of some fungicides on the fungal growth and pest control efficacy of B. bassiana or other entomopathogenic fungi through invitro or potted plant studies in multiple crop or pest situations. However, no information specific to the fungicides used in California strawberries is available, especially after the release of some new fungicides in the recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Only three fungicides (etridiazole, propamocard and mafanoxam) had no significant impact in vitro on spore germination or mycelial growth. Bruck (2009) found that, although a number of fungicides had a detrimental impact in vitro, most had no impact on M. anisopliae populations in bulk soil. The only exceptions were captan and triflumizolet, which had a detrimental impact on M. anisopliae populations in the rhizosphere.…”
Section: Cropmentioning
confidence: 94%
“…Often the best, most realistic approach is within the context of a field trial or at least outdoor, in-field microcosm. For instance, it was demonstrated that of 13 fungicides toxic in vitro, none had adverse impact on M. anisopliae in commercial potting media under realistic conditions, even when applied twice during the observation period (Bruck 2009a).…”
Section: Abiotic Factorsmentioning
confidence: 99%